(untitled) (Journal of the College of Education for Women, 2019)
The research is dealing with the color articulation and its significance in the poetry of Hana Al-bawab, who employed the “color” in a special technique in her poetry.The research is trying to deal with the identification of the color and its aesthetic significance and function in the poetic context, as it determines its indication and interaction with the words next to it in the context. The research will clarifies that the color is not only a visual phenomenon, but also an aesthetic, mental and emotional significance. The results that I have concluded, indicate that the poet has beseeched to display the color in her poetry with the plain and borrowed colors besides the inspired dark and bright colors. The color’s indication has been manifested through the colored picture, the senses correspondence and the opposite duality in Hana’s poetry.